Analisis Pengaruh Fundamental KeuanganPerusahaan Terhadap Harga Saham PerusahaanYang Tercatat Di Bursa Efek Indonesia - Winosa, Shilva Elwis (2016)
This study aims to investigate the influence of fundamental analysis (current ratio, return on investment, book value per share, debt to equity ratio, and the net profit margin) to share price. The sample in this study is a company listed on the Indonesia Stock Exchange. The sampling technique in this research is purposive sampling. Data analysis method used is the classic assumption test (normality test, autocorrelation, Multicolinearity, Heteroskedasitas) and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study meets the data for normal distribution. hypothesis testing showed a variable current ratio (t = 2,954), the variable return on investmen (t = 2.932), and book value per share (t = 8.927) had an influence on stock prices because it has the probability of value <0.05, while variable debt to equity ratio (t = 0.715) and net profit margin (t = -1.802) does not have penagruh on stock prices because it has the probability of value> 0.00. In the F test showed that together the variable current ratio, return on investment, the book value per share, debt to equity ratio, and the net profit margin significantly influence the share price. The coefficient of determination (R2) of 76.5 percent.